Qatar Climate Change Conference 2021 A Platform for addressing key climate change topics facing Qatar and the world - Tahir, Furqan (Hamad Bin Khalifa University Press, 2021)
Extreme heatwaves and rising wet-bulb temperatures would damage the human habitability of vital urban centers in the Middle East by the end of the 21st century, according to several published research documents, particularly in some regions in the Gulf Cooperation Council (GCC) countries. This may result in widespread social and economic disruptions and challenges driven by climatic change impacts in the rapidly growing urban areas of the Middle East. Middle East countries expect to face the major impacts of global warming due to the vulnerability of critical urban systems and infrastructure, and they are in necessity of developing climate change adaptation strategies to establish more robust urban centers resilient to climate change-driven events. Social and economic stability can be preserved by effectively preparing for the impending risks provided by climate change, allowing growth in a changing environment. The Qatar Climate Change Conference (QCCC), 2021, addressed key climate change topics of national importance to Qatar, bringing together high-level representatives from the public and private sectors. Understanding that climate change is the most pressing challenge facing the world today, the conference supports Qatar's ongoing contributions to global conversations around environmental policy and action.